2011
DOI: 10.1186/1478-4505-9-28
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of health policy guidelines for assisted reproduction in the Republic of Ireland, 2004-2009

Abstract: This analysis reports on Irish regulatory policies for in vitro fertilisation (IVF) from 2004-2009, in the context of membership changes within the Medical Council of Ireland. To achieve this, the current (2009) edition of the Guide to Professional Conduct & Ethics was compared with the immediately preceding version (2004). The statutory composition of the Medical Council from 2004-2009 was also studied. Content analysis of the two editions identified the following differences: 1) The 2004 guide states that IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…It has been published first in 2004 and more recently in 2009, which represents the last version [50, 52]. …”
Section: Resultsmentioning
confidence: 99%
“…It has been published first in 2004 and more recently in 2009, which represents the last version [50, 52]. …”
Section: Resultsmentioning
confidence: 99%
“…In all the countries analyzed it is allowed the realization of homologous and heterologous fertilization. [10][11][12][13][14][15] The anonymity of the heterologous fertilization is required only in Ireland, 14,15 although some clinics use the gametes of a known donor, 16 as realized in England. 12,13 In Norway, 11 the people generated from the AHR technologies can contact their donor after the age of 18.…”
Section: Discussionmentioning
confidence: 99%
“…The Ireland does not have a law that regulates the AHR, although there is a conduct guide named Guide to Professional Conduct and Ethics for Registred Medical Practitioners, published by the Medicine Federal Council. The first one was published in 2004 14 and reformulated in 2009 15 . It was stipulated in 2004 that the fertilized oocytes must be used to the implantation, and could not be discarded.…”
Section: Irelandmentioning
confidence: 99%
“…Work conducted in the United States has shown that medical student research activities can impact favourably on future careers; this outlet is not for everyone and many students do not think a research project should be required for graduation [9]. Although completing a research project was impossible given the module's brief duration, our students used this time to frame a research concept to which they later returned for completion-this generated downstream original research which was subsequently published with medical students as first [10] or second [11][12][13] author.…”
Section: Discussionmentioning
confidence: 99%